Pengaruh Perputaran Piutang terhadap Tingkat Profitabilitas (ROA) pada PT Enigma Cipta Humanika - K, Alinka Zeinayla; Ayu, Nabila Permata; Fadilah, Anggi Rahman; Akbar, Muhammad Malik; Yusuf, Ahmad Muhammad (Sekolah Tinggi Ilmu Ekonomi Yasa Anggana Garut, 2026)
This study aims to determine the effect of accounts receivable turnover on the level of profitability as measured by Return on Assets (ROA) at PT Enigma Cipta Humanika. This research uses a quantitative research method. The data sources were obtained from the Balance Sheet and Income Statement of PT Enigma Cipta Humanika for the period 2020 to 2022. The secondary data were analyzed using Simple Linear Regression Analysis, Correlation Coefficient Test, and Coefficient of Determination Test. This study employed SPSS version 22.0 as the analytical tool. The result of the simple linear regression equation is Y = 0.021 − 0.002X. The result of the correlation coefficient (R) test is −0.025. The coefficient of determination is 0.1%, while the remaining 99.9% is influenced by other factors not examined in this study. These results indicate that accounts receivable turnover has no significant effect on the level of profitability (ROA).